ANALISIS KEBUTUHAN AIR DOMESTIK DAN NON DOMESTIKDI KABUPATEN GUNUNGKIDUL - Farida Afriani Astuti; Andi Sungkowo; Wisnu Aji Dwi Kristanto (Jurnal Sains & Teknologi Lingkungan, 2018)
Water is a key and significant factor in sustaining human life. Variations in the amount of water needed dependant on each region, due to some factors such as the population of all things living and their activities. The north part of Kabupaten Gunungkidul is one example of an area with a lack access to of constant water. The objective of this study is to calculate the water need in the research area of Kabupaten Gunungkidul. The water need calculation is based on domestic and non-domestic demands. Domestic demand consists of the use of water for drinking, bathing, washing, using the toilet, and washing vehicles. It is usually based on the age group, ranging 0-15, 16 -65, and > 65 years old. The non-domestic water is consumed by chicken livestock, goat and cattle farm, and general farming. The data for this study was obtained via a questionnaire as a survey tools. Descriptive statistics methods are used to analyse the data. The varied domestic demand comprised age groups due to their activities.Total daily amounts consumed varied by age group vary from 0, 16-65, and > 65 years old amounting to 32.43 to 91.43, 41 to 113.87, and 38.71 to 105.21 litres per person per day. Non-domestic water needs for livestock, goat farm, and cattle farm were amounted to respectively 0.5, 5, 20 litres per day.